The impact of covid-19 on the Malaysian stock market: evidence from an autoregressive distributed lag bound testing approach - Awadh Ahmed Mohammed Gamal (Tanjong Malim, 2021)
The impact of covid-19 on the Malaysian stock market: evidence from an autoregressive distributed lag bound testing approach by Awadh Ahmed Mohammed Gamal